Silencing of juvenile hormone epoxide hydrolase gene (Nljheh) enhances short wing formation in a macropterous strain of the brown planthopper, Nilaparvata lugens. (October 2017) - Zhao, Jing; Zhou, Yunlong; Li, Xiang; Cai, Wanlun; Hua, Hongxia
Graphical abstract: Highlights: Nljheh cDNA was cloned and analyzed in Niliparvata lugens . Nljheh and Nljhe show a strain-specific expression pattern. Silencing of Nljheh enhances short wing formation in macropterous females. Abstract: The rice brown planthopper, Nilaparvata lugens, is an important migratory pest in many rice planting areas of Asia. The typical wing dimorphism of N. lugens gives them flexibility to adapt to different environmental cues. As an important hormone in the insect's endocrine regulation, juvenile hormone (JH) has previously been shown to participate in the wing morph determination of N. lugens . In this paper, we investigated the possible wing morph determination roles of two JH metabolic enzymes, JH esterase (JHE) and JH epoxide hydrolase (JHEH). A 1957-bp full-length cDNA sequence encoding JHEH in N. lugens (NlJHEH) was first cloned from a hemipteran insect. Except for an uncertain transmembrane segment prediction, the deduced 454-amino-acid sequence of Nljheh has all of the conserved domains of JHEHs such as the H 147 GWP 150, Tyr293 and Tyr368 motif corresponding to the oxyanion hole and the residues Asp222, Glu398, and His425 in the catalytic triad. qRT-PCR results showed that both Nljhe and Nljheh had different expression timeframes between a predominantly brachypterous strain (BS) and a macropterous strain (MS) of N. lugens, indicating that these two enzymes may participate in wing dimorphism regulation in brown planthopper. Silencing Nljheh expression by dsRNA injection enhanced short wing formation in the macropterous strain of N. lugens, while the brachypterizing individuals were mainly females. Compared to the dsgfp injection control, silencing Nljhe had no brachypterizing effect. Our results indicated that NlJHEH plays an important role in the wing morph determination of N. lugens .